Nutrient deficiency symptoms in yams (Dioscorea spp.) - Shiwachi, H.; Okonkwo, C.; Asiedu, Robert (Wiley, 2004)
Symptoms of nutritional deficiencies in D. alata and D. rotundata were observed when yam plants were grown in nutrient solutions from which any of the following had been omitted: N, P, K, Ca, Mg, Zn, Fe, B, Mn, Cu and Mo. The symptoms of deficiency of major elements were visible on plants of both species. The omission of Fe, B and Mo produced characteristic symptoms on the leaves of D. rotundata, but D. alata showed symptoms only in response to Fe deficiency. The omission of minor elements led to poor growth of the leaves, stems and roots. Nutrient deficiencies in yam plants could be diagnosed by visual symptoms in the field.